Results of a systematic search for outburst events in 1.4 million galaxies. Issue 1 (4th October 2018) - Drake, A J; Djorgovski, S G; Graham, M J; Stern, D; Mahabal, A A; Catelan, M; Christensen, E; Larson, S
ABSTRACT: We present an analysis of 9 yr of Catalina Surveys optical photometry for 1.4 million spectroscopically confirmed SDSS galaxies. We find 717 outburst events that were not reported by ongoing transient surveys. These events have time-scales ranging from weeks to years. More than two-thirds of these new events are found in star-forming galaxies, while such galaxies only constitute ${\sim }20{{\ \rm per\ cent}}$ of our sample. Based on the properties of the hosts and events, we find that almost all of the new events are likely to be associated with regular supernovae. However, a small number of long time-scale events are found among the galaxies containing AGNs. These events have similar properties to those recently found in the analyses of light curves of large samples of AGNs. Given the lack of such events among more than a million passive galaxies in the sample, we suggest that the long outbursts are associated with supermassive black holes or their environments.